Analysis of the Solid Medical Waste Management System at Tk.II Hospital 14.05.01 Pelamonia Makassar (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Hospitals produce medical and non-medical waste, solid waste and liquid waste. Solid medical waste has a significant impact on the environment, therefore hospitals must manage solid medical waste as optimally as possible. By managing solid medical waste in accordance with regulations, hospitals will not pollute the surrounding environment and the health and safety of medical and non-medical workers can be guaranteed. This research aims to analyze the solid medical waste management system at Tk.II Hospital 14.05.01 Pelamonia Makassar. The method used in this research is qualitative research with a descriptive approach in the form of written or spoken words. The informants in this research were 5 people with data obtained through in-depth interview observations, namely conducting direct observations in the field and documentation studies during the research. The results and conclusions show that the hospital has managed solid medical waste in accordance with the Regulation of the Minister of Health of the Republic of Indonesia (Permenkes RI) Number 7 of 2019, namely appropriate human resources, standard operational procedures that have been carried out well, budgets that are managed according to the waste produced, adequate facilities and infrastructure, the solid medical waste management process starting from sorting to appropriate temporary storage, and finally final processing through partners or third parties in collaboration with the hospital which has been carried out well.